HUBUNGAN ANTARA INDEKS MASSA TUBUH DENGAN KEJADIAN EARLY MENARCHE PADA SISWI SEKOLAH DASAR - Novy Isni Kurniyati; Riri " Novayelinda; Bayhakki " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Early menarche is the first menstruation period that happened before 12 years old. One of the influence caused early menarche is nutrients. The status of nutrition was identified based on Body Mass Index (BMI). This research aims to identify the correlation between body mass index and the prevalence of early menarche on elementary schoolgirls. The design of this research was descriptive correlation with cross sectional approach. This research was conducted in SDN 006 and SDN 012 Tualang with 276 samples which were selected by using total sampling. Questionnaire and anthropometric standard book released by Indonesian Health Minister used as instrument. This research used univariat analysis and chi-square. The result shows that there was a correlation between body mass index and the prevalence of early menarche on elementary schoolgirls with p value (0,001) < (0,05). It is expected for the next researcher to do more research about early menarche and correlated with different variable. Key words: Body Mass Index, early menarche, elementary schoolgirls